A Rare Mutation in Patients With Resistance to Thyroid Hormone and Review of Therapeutic Strategies. (September 2015) - Lai, Shuiqing; Zhang, Shuting; Wang, Long; Chen, Zhijiang; Fu, Xiaoying; Jianhao, Pei; Chen, Hongmei; Kuang, Jian
Abstract: Background: Resistance to thyroid hormone (RTH) is a rare syndrome characterized by elevated thyroid hormone (TH) along with nonsuppressed thyroid-stimulating hormone (TSH). The clinical symptoms can vary considerably, and no definite treatment has been established thus far. Methods: A family with RTH harboring a TH receptor (THR)-β gene mutation (A234T) is described, the therapeutic strategies for RTH are reviewed, and optimization of the treatment strategies was attempted. Results: Gene sequencing revealed a point mutation (A234T) in the THR-β gene of the proposita, her elder brother and her mother. During the 20-month follow-up period, it was found that the proposita experienced apparently higher TSH level and normal TH level on taking antithyroid medication. However, on discontinuing the medication, her thyroid function returned to the baseline of elevated FT3, FT4 level along with inappropriately normal TSH. Thus far, there is no guideline regarding the treatment strategies for the RTH. Antithyroid drugs are effective for patients with thyrotoxic symptoms but pose an increased risk of thyrotroph hyperplasia. The efficacy and safety of D-T4 and bromocriptine still remains debatable, TRIAC may be the most promising drug, as it is effective and can reduce both TH and TSH level. However, L-T3 or L-T4 may be necessary for some RTH patients who exhibit massive goiter or hypothyroid symptoms. Conclusions: It is demonstrated in this article that the A234T mutation in the THR-β gene can cause the RTH. Treatment of this condition is challenging, and individualized therapy is required because of the variable clinical features.